Konsep-Konsep Tasawuf dan Relevansinya dalam Kehidupan - Arrasyid Arrasyid (IAIN Bengkulu, 2020)
The rapid development of the times has positive and negative impacts on life. Moral and spiritual degradation is one of the negative impacts that emerge like humans living without a clear purpose. Resulting in high crime both drug abuse, juvenile delinquency and so on. These problems make humans a cause as well as those responsible for solving them. Meanwhile conceptually the problem is closely related to personality problems or in Islam is called morals. The purpose of this study is to describe and review the concepts of Sufism and its relevance in everyday life. This research is a Library ResearchBecause of that the data source is in the form of library materials such as books, journals and scientific articles. In accordance with the type, the data collection in this study uses library research methods which are analyzed using the method of description and data analysis . The h acyl of pe nelitian this is maqamat and ahwal shown are by Abu Nasr al-Sarraj, the author of Al-Luma ': Reference Complete Science of Sufism , which maqamat that there are seven, namely: repentance, wara, ascetic, fakir, patient, trust, and pleasure. The ahwal are muraqabah , mahabbah, khauf, raja', syauq,' uns, tuma'ninah, musyahadah , and sure. The relevance of the concepts of Sufism to present life is that these concepts will become a guideline for achieving a true approach to God.